STRATEGI AISYIYAH PIMPINAN CABANG KARANGANYAR DALAM PEMBERDAYAAN PEREMPUAN SEBAGAI USAHA PEMENUHAN HAK EKONOMI WARGA NEGARA - Ayun Mangesti; Rini Triastuti; Wijianto (Jurnal PPKn, 2019)
The objectives of the research are: (1) to find out the strategy of Aisyiyah Leadership of Karanganyar Branchin the women's empowerment in Karanganyar District as an effort to fulfill the citizens? economic rights (2) to find out the supporting factors and inhibiting factors experienced by Aisyiyah Leadership of Karanganyar Branchin women?s empowerment as an effort to carry out the fulfillment of citizens? economic rights strategies. The research approach used by the researcher is a qualitative descriptive using document/ content analysis. The data sources are obtained from informant, place, event, and document. The research subject used was purposive sampling and snowball sampling. The data collection techniques werean interview, observation, and document analysis. Data triangulation and triangulation methods are used to obtain the data validity. Whereas, the technique of analyzing the data using an interactive analysis model with the following stages: 1) data collection, 2) data reduction, 3) data presentation, and 4) conclusions. Moreover, the research procedures used are the following steps: 1) preparation, 2) data collection, 3) data analysis, 4) preparation of research reports. Based on the result of this research, it can be concluded that: (1) the strategy of Aisyiyah Leadership of Karanganyar Branch in women?s empowerment as an effort of women's economic rights fulfillment for their members have been carried out, but not all have worked smoothly. The collaboration strategy of Aisyiyah with other agencies in terms of the women's empowerment, namely PPA and BPPKI Karanganyar can be held well according to the program objectives. The empowerment assistance strategy cannot be implemented as expected before because there are still several obstacles. (2) the supporting factors strategy of Aisyiyah Leadership of Karanganyar Branchare particular attention about the women?s empowerment for the women's economic rights fulfillment and cooperation or good relations with other agencies in terms of the women's empowerment. The inhibiting factors in Aisyiyah Muhammadiyah's strategies are the human resources which were not ready yet, a lack of active number administrators, and there are no independent funding sources.   Full Paper